2007
DOI: 10.1055/s-2007-948212
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Cushing's Syndrome Due to Concurrent Corticotropin-Releasing Hormone (CRH) and Adrenocorticotropic Hormone (ACTH) Secreted by Malignant Gastrinoma

Abstract: Ectopic Cushing's syndrome due to various malignancies is not uncommon. However, a few cases of ectopic Cushing's syndrome caused by corticotropin-releasing hormone (CRH), or CRH with adrenocorticotropic hormone (ACTH) have been reported. A 28-year-old woman presented with acute upper gastrointestinal bleeding caused by an active ulcer, located atypically in the 2nd portion of duodenum. Further work-up revealed high gastrin levels and abdominal computed tomography (CT) scans showed a large pancreatic head mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…However, these studies need to be confirmed using peptide-specific antibodies that discriminate between CRF and the homologue urocortins. In a later study, a 28-year-old woman, described with upper gastrointestinal bleeding caused by an active ulcer, a pancreatic head mass, and multiple liver metastases, was found to have a CRF-positive liver biopsy by immunohistochemical analysis [70].…”
Section: Crf and Gastrointestinal Cancersmentioning
confidence: 99%
“…However, these studies need to be confirmed using peptide-specific antibodies that discriminate between CRF and the homologue urocortins. In a later study, a 28-year-old woman, described with upper gastrointestinal bleeding caused by an active ulcer, a pancreatic head mass, and multiple liver metastases, was found to have a CRF-positive liver biopsy by immunohistochemical analysis [70].…”
Section: Crf and Gastrointestinal Cancersmentioning
confidence: 99%
“…A recently published study in children and adolescents reported that, in 3 out of 7 patients with ectopic ACTH/CRH syndrome, the primary tumor was located in the pancreas [6]. In adults, apart from pNET, ACTH/CRH co-secretion is described in thymic and bronchial carcinoids, pheochromocytomas, medullary thyroid cancer, and lung cancer [2,4,5,[7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 95%
“…In 1993, Saeger et al described the first case of an islet cell carcinoma in which ACTH along with CRH secretion was present [4], following which another two cases of pNETs co-secreting ACTH and CRH were reported [2,5]. A recently published study in children and adolescents reported that, in 3 out of 7 patients with ectopic ACTH/CRH syndrome, the primary tumor was located in the pancreas [6].…”
Section: Discussionmentioning
confidence: 97%
“…There are reports in literature on the concurrent CS and pheochromocytoma [3,4], sarcoidosis [5], pancreatic acinar cell carcinoma [6], pre-eclamptic findings [7], malignant gastrinoma [8], bronchial carcinoid lung tumor [9], pancreatic neuroendocrine tumor [10], Hippel-Lindau disease [10], or mesenteric neuroendocrine carcinoma [11]. Our patients had nothing of these associations.…”
Section: Discussionmentioning
confidence: 95%